TRANSFORMATION EFFECTS OF BASICO-MOTORICAL ABILITIES UNDER INFLUENCE OF EXPERIMENTAL PROGRAMME AT THE VOLLEYBALL PLAYERS STRATURE 16 TO 18 YEARS - Azer Korjenić; Miloš Jelčić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Volleyball at the time, with her evolution, from the very sample game, development to the very nice, complex game, with a lot very atractive actions which from the volleyball players order antropological predispositions, necsarry level of technical and tactic knowledge high level of conditions of player which they at all game could play wuth high tempo and force. If we want to satisfied all criteries of successfull in volleyball game, it is necessary to give player qualitative trenning-process, with apply of modern technology and models of training, but also the fizical prepare of volleyball players is very importatnt (Šoše, 2002) . The basic target of this exploration was to confirm quantative and qualitative level of transformations effects of motorical status volleyball players strature from 16 to 18 years, under influence applying experimental progamme of training work in frame of basic prepare. The results of this exploration show us that applyed training programme give significant quantative and qualitative effects between motorical status explorated sample, especially in the way of parametars for scale segmentar speed of inferior and superior extremitates, and coordination of steps. So, applayed training technology in frame this experimental prgramme, showed us as the very effective for basic prepared of young volleyball players.